A world of difference ‐ opportunities for applying the 1972 World Heritage Convention to the High Seas. (September 2017) - Laffoley, Dan; Freestone, David
Abstract: The 1972 World Heritage Convention has not to date been applied to marine areas beyond national jurisdiction (ABNJ), i.e. to high seas and deep sea bed sites. Examples are given of high seas and deep seabed sites that appear to meet the criteria of Outstanding Universal Value for inscription. The ongoing negotiations at the United Nations for a new International Legally Binding Instrument (ILBI) on the conservation and sustainable exploitation of biodiversity in ABNJ are highlighted as a significant complementary initiative. Three feasible modalities are suggested by which the Parties to the 1972 Convention might be able to allow inscription of sites in ABNJ and establish appropriate management regimes: incremental and pragmatic agreement to minor changes in the way that they apply the treaty or formally announcing a change in the way that they intend to apply a treaty among themselves in the future; agreeing to an Amendment outside the terms of the 1972 Agreement; or developing an optional protocol to the 1972 Convention could be developed through an international negotiation among States Parties, binding only on those States that choose to ratify any resulting protocol. The merits of these different options are explored. Under any scenario, a system will also need to be elaborated for the protection of World Heritage sites in areas beyond national jurisdiction. This will be an important undertaking which will require collaboration between UNESCO and the relevant competent international organizations and their States Parties.